Proposal of Machine Learning Approach for Identification of Instant Messaging Applications in Raw Network Traffic - PektaÅ, Abdurrahman (International Journal of Intelligent Systems and Applications in Engineering, 2018)
Identification of Internet protocol from either raw network traffic or either network flows plays a crucial role at maintaining and improving the security of computer systems. A significant amount of research is carried out while exploiting a variety of identification techniques.  Although certain level in success at detection of network protocols for unencrypted traffic has been achieved, accuracy and performance is rather poor for encrypted traffic.  Considering technological trends, new and existing applications have been adopted to use encryption mechanism to protect information and privacy. Therefore, classification of encrypted network traffic is mandatory for ensuring security. Moreover, while performing network forensic investigation, labelling of network protocols/applications is a must to accomplish. In this study, we propose a method to automatically identify instant messaging applications from raw network traffic. To this end, we first extract flow based static features from network capture and then apply machine learning algorithms. The proposed method is evaluated with fairly large dataset. The dataset compromise of publicly available NISM dataset and the network traffic of 9 popular instant messaging applications collected in a controlled environment. The dataset overall contains 716607network flows belonging to 20 application categories. The proposed method classifies network flows of instant messaging applications into their corresponding application categories with the accuracy over 0.99 and F1-score of 0.99.